2011
DOI: 10.15288/jsad.2011.72.833
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Drinking Norms: For Whom Does Reference Group Matter?

Abstract: ABSTRACT. Objective: Perceived descriptive drinking norms often differ from actual norms and are positively related to personal consumption. However, it is not clear how normative perceptions vary with specifi city of the reference group. Are drinking norms more accurate and more closely related to drinking behavior as reference group specifi city increases? Do these relationships vary as a function of participant demographics? The present study examined the relationship between perceived descriptive norms and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 59 publications
7
75
1
1
Order By: Relevance
“…This supports earlier research which suggested that although general norms are important, the norms of close friends are even more influential (Cho, 2006). The standard prevention practice on college campuses usually involves social norms campaigns with the understanding that local norms data (i.e., specific college norms) are more powerful than broader regional or national stats in combating faulty perceptions (Larimer et al, 2011;Lewis & Neighbors, 2006). Our findings indicate that prevention campaigns might need to go even one step further.…”
Section: Social Tiessupporting
confidence: 88%
“…This supports earlier research which suggested that although general norms are important, the norms of close friends are even more influential (Cho, 2006). The standard prevention practice on college campuses usually involves social norms campaigns with the understanding that local norms data (i.e., specific college norms) are more powerful than broader regional or national stats in combating faulty perceptions (Larimer et al, 2011;Lewis & Neighbors, 2006). Our findings indicate that prevention campaigns might need to go even one step further.…”
Section: Social Tiessupporting
confidence: 88%
“…Our study suggests that the effect of drinking norms may be contingent on social distance from peers. Although perceived norms for the "typical student" are less accurate (i.e., easier to correct) than norms for more specifi c/similar referent groups (at least in college students; Larimer et al, 2011), priority should be given to correct misperceptions of similar referent groups given their greater infl uence on alcohol-related behaviors (Lewis and Neighbors, 2006). Programs targeted to delay age at initiation may be more effective if their focus is on resistance to friend offers rather than more general resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors report that social norms regarding substance use highly affect adolescents and young adults (Dennhardt & Murphy, 2013). College students who overestimate the extent to which their social environment uses a substance (the descriptive norm), tend to use that substance more themselves (e.g., Larimer et al, 2011;Lewis et al, 2011;Martens et al, 2006;McMillan & Conner, 2003). Subjective norms, the extent to which an individual feels it is expected of them to (not) take a substance, can be subdivided into injunctive norms, i.e., the perceived (dis)approval by others regarding substance use, and motivation to comply, i.e., the wish (not) to comply with this norm (Ajzen, 1991).…”
Section: Introductionmentioning
confidence: 99%